Changing Management of Clinical Low-Stage Testicular Cancer - Timothy Gilligan (The Scientific World Journal)
Stage I and II testicular germ cell tumors (GCTs) are almost always cured with appropriate treatment and most ongoing research regarding these tumors focuses on minimizing treatment toxicity. The management of clinical stage I testicular GCTs has grown more complicated due to the emergence of a brief course of chemotherapy as an additional treatment option for stage I seminomas and stage I nonseminomas. In addition, growing concern about radiation-induced cancers and other late toxicity has dulled enthusiasm for radiotherapy as a treatment for stage I seminomas. However, recent randomized trials have shown that radiotherapy doses and field sizes can be lowered without compromising cure rates and it is possible that this reduction in radiation exposure will reduce the rate of secondary cancers. At this point in history, stage I patients have three treatment options following radical orchiectomy: adjuvant (sometimes called “primary”) chemotherapy (carboplatin for seminomas and the combined regimen of bleomycin, etoposide, and cisplatin for nonseminomas), surveillance, and either retroperitoneal lymph node dissection (for nonseminomas) or radiotherapy (for pure seminomas). Clinical studies have made it possible to identify subgroups of patients at high and low risk for relapse and this has made it possible to tailor treatment decisions to the individual patient's postorchiectomy relapse risk.